Trait and Flourishing in Emerging Adulthood: Examining the role of Protective Factor and Risk Factor as Mediator - Edwina, O. Irene Prameswari; Sembiring, Tessalonika; Jeans Esparanci (Analitika: Jurnal Magister Psikologi UMA, 2024)
The aim of this study is to obtain an overview of the mechanism of the role of traits on flourishing in young adults with protective factors and risk factors as mediators. Data were collected using flourishing questionnaire, traits questionnaire, protective factors questionnaire and risk factors questionnaire. The sampling technique used was accidental sampling, with 202 emerging adults (18-25 years.  Data were processed using mediation analysis model 4 of SPSS PROCESS (Hayes, 2018).  The results showed that trait extraversion, openness, agreeableness, and conscientiousness had a direct, strong, significant impact with a positive direction on flourishing. Trait agreeableness has the strongest direct impact on flourishing compared to the other three traits. Risk factors mediate all five traits on flourishing, while protective factors only mediate trait extraversion on flourishing. Protective factors play less of a role as a mediator variable. Risk factors played a greater role in flourishing (negative direction) than protective factors (positive direction). Protective factors can help individuals overcome life challenges and enhance their well-being. However, if risk factors predominate, protective factors may not be strong enough to maintain or improve growth.  Therefore, individuals must have the skills to manage risk factors